2014
DOI: 10.1111/bij.12267
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal cline in allele length provides evidence for selection in a circadian rhythm gene

Abstract: Divergent natural selection across a heterogeneous landscape can drive the evolution of locally adapted populations in which phenotypic variation is fine‐tuned to the environment. At the molecular level, such processes can be inferred by identifying correlations between genetic variation and environmental variables. We demonstrate that allele length and allele frequency at a regulatory circadian rhythm gene, OtsClock1b, are highly correlated (R2 = 0.86, P = 1.25 × 10−5) with latitude (a surrogate for photoperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…In D. littoralis , the rate at which the circadian rhythm damps out and eclosion becomes arrhythmic increases with latitude (Pittendrigh et al, 1991). A latitudinal cline in allele-length at the OtsClock1b locus was found in kokanee salmon populations in both North America and Russia (Lemay and Russello, 2014). A study of 52 human populations revealed a significant correlation between single nucleotide polymorphisms in circadian-regulated genes and latitude-derived difference between maximum and minimum photoperiod; this suggests that, following migration out of Africa, humans adapted to different latitudes in part through adjustments to their circadian clocks (Forni et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In D. littoralis , the rate at which the circadian rhythm damps out and eclosion becomes arrhythmic increases with latitude (Pittendrigh et al, 1991). A latitudinal cline in allele-length at the OtsClock1b locus was found in kokanee salmon populations in both North America and Russia (Lemay and Russello, 2014). A study of 52 human populations revealed a significant correlation between single nucleotide polymorphisms in circadian-regulated genes and latitude-derived difference between maximum and minimum photoperiod; this suggests that, following migration out of Africa, humans adapted to different latitudes in part through adjustments to their circadian clocks (Forni et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…; O'Malley and Banks ; O'Malley et al. ; Lemay and Russello ) and probably reflects local adaptation to different photoperiodic regimes (Kyriacou et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphism at a Clock polyglutamine-rich region (Poly-Q) has been reported both among and within populations (e.g., Johnsen et al 2007;O'Malley and Banks 2008;Liedvogel et al 2009;Caprioli et al 2012), and it may play a role in determining phenological responses by differentially affecting the timing of seasonal activities (Hayasaka et al 2002). At the amongpopulation level, a latitudinal cline in Clock allele size, with the frequency of longer alleles increasing along a southnorth gradient, has been documented in some migratory bird and fish species (Johnsen et al 2007;O'Malley and Banks 2008;O'Malley et al 2010;Lemay and Russello 2014) and probably reflects local adaptation to different photoperiodic regimes (Kyriacou et al 2008). However, such a latitudinal cline has not been detected in other studies (e.g., Dor et al 2012;O'Brien et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Across a broad latitudinal range, genetic differences in OtsClock1b were found among populations of Chinook salmon, coho salmon ( O. kisutch ), pink salmon ( O. gorbuscha ), and chum salmon ( O. keta , O'Malley and Banks; O'Malley et al. ), as well as kokanee (Lemay and Russello ). Moreover, RLS have never been shown to differ between seasonal runs or to vary systematically with latitude.…”
Section: Discussionmentioning
confidence: 99%
“…We also predicted differentiation at circadian-linked loci, because of their role in the regulation of seasonal timing. In salmon, OtsClock1b is one of two duplicated clock genes, and length polymorphisms of the PolyQ domain are known to vary among populations with distinct reproductive timing at different scales (O’Malley et al 2007 , 2010 ; O’Malley and Banks 2008 ), including in kokanee (Lemay and Russello 2014 ).…”
Section: Introductionmentioning
confidence: 99%